Exploring the peripheral crosstalk between dopamine and NPY in the regulation of energy balance - Lopes, Eduardo José Baptista (2023)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia